Reaction behavior, microstructure, and mechanical properties of FeAl-316 stainless steel joints - CAI Xiaoping; YIN Jinnan; ZHANG Zhipeng; FENG Peizhong (Fenmo yejin jishu, 2024)
The effective joining between the FeAl intermetallic compounds and the 316 stainless steels was realized by the combination of thermal explosion reaction and powder metallurgy. The effect of joining temperature (700, 800, 900 ℃) on the interface composition and mechanical properties were studied. The results show that, the temperature of FeAl reaction layer rises to 1050 ℃ instantaneously when it is heated to 637 ℃, and the obvious thermal explosion reaction occurs, accompanied by the intense heat release lasting about 15 s. With the increase of joining temperature from 700 ℃ to 900 ℃, the interface is composed of Fe-316SS and 316SS(Al) alternately, which is transformed into FeAl-316SS(Al)-316SS. Sound metallurgical bonding is formed at all these three temperatures. When the joining temperature is 800 ℃, the shear strength reaches 75 MPa.